Implementation of Akidah Akhlak Principles in Facing Moral Challenges in MTS Maárif NU School Youth - Sabrina, Neyla (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
Speaking about the implementation of the principles of morality in schools, it turns out there are impeding factors of the smooth implementation in schools including in MTS Maárif NU, then raised this issue and studied. Among the obstacles are uncomprehensible behavior, such as dirty speech, smoking, schoolgirls who don't wear a sword and all the students who haven't performed prayer on time. Starting from these questions, he made articles related to the implementation of the principles of morality in the face of moral challenges in the youth school MTS Maarif NU with the aim of answering all the questions that exist in the present time. Through a qualitative approach as well as using the method of study this library analyzes about the principles of morality that are applied in the school to face various challenges in teenagers at MTS Maárif NU school. The results of this research find that on the implementation of the principle of legality to face teenagers in Mts Maarif NU school is performed in the best possible good that appears in the learning of ethics that has been implemented in school activities. The school's activities in addressing the issue are sholat jamaah, social service, study/ ta'lim at the end of the semester and the pilgrimage of thr guardian.